TakyÄ«f Fiqh Pembayaran Jasa Transportasi Online Menggunakan Uang Elektronik (Go-Pay dan OVO) - Wijaya, Hendra (NUKHBATUL 'ULUM: Jurnal Bidang Kajian Islam, 2018)
This research explains differences of opinion among muamalah experts contemporary about takyif fiqh (deriving law) of transactions in the use of Gopay and OVO as a means of payment (electronic money) on online transportation services, where there are at least four disputed takyifs, namely al-ijÄrah alMausÅ«fah Fi al-Å»immah, WadÄ«ah, Qard á¹£ , and á¹¢ á¹£ arf. The differences of takyif fiqh á¹£ has implications for the differences of law consequences between legal and illegal transactions in using Go-pay and OVO, this research explained that it is more effective to derive the law according to the á¹¢arf contract that is more appropriate than the other contracts, the substance of Go-pay and OVO top up process is the conversion of two similar currency between paper money to electric money. Because á¹¢arf contract is the most appropriate form of contract in this transaction, the discount acquired by the consumer from the Go-Pay and OVO payment is considered ataya (gift) that is legal without any usury.